Ceramic molybdenum-manganese metallization slurry, metallized ceramic part and preparation method thereof

The molybdenum manganese metal layer is solved by using ceramic molybdenum manganese metallization slurry, ceramic metal powder containing molybdenum powder, manganese powder and ceramic powder and a binder solution of polymers with hydrophilic monomers and hydrophobic monomers. The problem of uneven distribution of the surface of small-sized ceramics achieves a uniform thickness of metal layer, saving metal usage, and improving welding strength and flatness.

CN116621597BActive Publication Date: 2025-02-07HUNAN UNIV OF HUMANITIES SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310345155.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-02-07
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

In the prior art, the molybdenum manganese metal layer is unevenly distributed on the surface of small-sized ceramics, resulting in reduced welding strength, waste of precious metals and increased costs, and is not suitable for subsequent sintered nickel-covered process.

Method used

A ceramic molybdenum-manganese metallization slurry is used, including ceramic metal powder and binder solution. The ceramic metal powder consists of molybdenum powder, manganese powder and ceramic powder. The binder solution is composed of hydrophilic monomers and hydrophobic monomers. The polymer composition is made of a uniform thickness of molybdenum manganese metallization layer by adjusting the mass ratio of raw material components and binder.

Benefits of technology

A uniform distribution of the molybdenum-manganese metal layer is achieved, with a relative average deviation of less than 2%, saving more than 50% of the molybdenum-manganese consumption, reducing high-temperature expansion, increasing welding strength, and providing good flatness conditions, reducing silver The amount of copper solder used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116621597B_ABST
    Figure CN116621597B_ABST
Patent Text Reader

Abstract

The present invention discloses a ceramic molybdenum-manganese metallization slurry, a metallized ceramic part and a preparation method thereof, wherein the ceramic metallization slurry comprises the following raw material components: ceramic metal powder, a binder solution, the mass ratio of the ceramic metal powder to the binder solution is (0.5-3): 1, wherein the ceramic metal powder comprises the following components by weight: 60-86 parts of molybdenum powder, 7-20 parts of manganese powder, and 7-20 parts of porcelain powder; the binder solution comprises a binder and water, the mass ratio of the binder to water is (0.2-1.5): 1, and the binder is a polymer having both a hydrophilic monomer and a hydrophobic monomer. The thickness of the molybdenum-manganese metallization layer made of the ceramic metallization slurry provided by the present invention can be controlled at 5-30 microns, the thickness deviation of the entire metal layer is less than 2%, and there is no groove in the prior art, which can not only save the amount of molybdenum-manganese and silver-copper precious metals, but also the thinner molybdenum-manganese layer can reduce the expansion at high temperature and increase the welding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic packaging, and in particular to a ceramic molybdenum-manganese metallization slurry, a metallized ceramic part and a preparation method thereof. Background Art

[0002] Oxide ceramics or nitride ceramics are widely used in the packaging of electronic current and power components. In the packaging process, the ceramic surface must generally be metallized first. Most of the existing technologies first metallize the ceramic surface with molybdenum and manganese, and then weld it to the metal part with solder after nickel coating. The thickness uniformity of the molybdenum and manganese metal layer is the key to the reliability of welding between ceramic and metal parts, especially for small sizes (welding end face less than 1mm).

[0003] At present, the molybdenum-manganese metallization process is to first disperse the molybdenum-manganese metal powder into the ethyl cellulose pine alcohol solution to form a slurry, and then apply it to the ceramic surface and undergo high-temperature treatment to finally obtain a molybdenum-manganese metal layer. However, due to the effects of slurry stability and surface tension, during the drying process, small-sized end faces are prone to form grooves with thick sides and thin in the middle due to the mismatch between the surface tension of the slurry and the surface tension of the ceramic substrate. After the subsequent high-temperature treatment to form a molybdenum-manganese metal layer, this groove still exists, and the relative average deviation of thickness is greater than 30%. This phenomenon will bring many disadvantages, such as: (1) the groove is prone to cause cold solder joints, reducing the welding strength; (2) in order to reduce the cold solder joints caused by the groove, the thickness of the silver-copper solder sheet is often increased to fill the groove, which in turn causes waste of precious metals and increased costs; (3) in order to ensure that the groove is also covered by molybdenum-manganese metal, the thickness of the molybdenum-manganese coating must be increased, and the thickest part is often greater than 30 microns. In fact, a thicker molybdenum-manganese layer will cause a larger expansion at high temperature or the expansion size of the thicker and thinner molybdenum-manganese layers will be inconsistent, reducing the welding strength and increasing costs; (4) it is not suitable for the subsequent sintering nickel coating process, because more nickel slurry must be coated on the groove than on both sides, which is easy to cause the nickel layer to crack. Therefore, it is urgent to develop a new molybdenum-manganese slurry formula to solve the series of problems caused by the uneven distribution of the molybdenum-manganese metal layer on the surface of small-sized ceramics. Summary of the invention

[0004] The invention provides a ceramic molybdenum-manganese metallization slurry, a metallized ceramic part and a preparation method thereof, so as to solve the technical problem of uneven distribution of the molybdenum-manganese metal layer on the ceramic surface.

[0005] According to one aspect of the present invention, a ceramic molybdenum-manganese metallization slurry is provided, comprising the following raw material components: ceramic metal powder and a binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is (0.5-3):1,

[0006] The ceramic metal powder comprises the following components in parts by weight: 60-86 parts of molybdenum powder, 7-20 parts of manganese powder, and 7-20 parts of porcelain powder; the binder solution comprises a binder and water, the mass ratio of the binder to water is (0.2-1.5):1, the binder is a polymer containing both a hydrophilic monomer and a hydrophobic monomer, the mass ratio of the hydrophilic monomer to the hydrophobic monomer is 1:(0.15-18),

[0007] The structural formula of the hydrophobic monomer is CH2=CR 1 R 2 , where R 1 is -H or -CH3; R 2 -CN, -C6H5, -COOR 3 , where R 3 is an alkyl group, a cycloalkyl group or an aromatic group;

[0008] The structural formula of the hydrophilic monomer is: CHR 4 =CR 5 R 6 , where R 4 and R 5 All are -H or -CH3 or -COOM; R 6 -COOM, -CH2COOM, -COO(CH2)6SO3M, -CONH2, -CONHR 7 , where R 7 is an alkyl group or a cycloalkyl group; M is an H element or any one of the metal elements involved in the ceramic metal powder.

[0009] Furthermore, the particle size of the molybdenum powder and the manganese powder is less than or equal to 10 microns.

[0010] According to another aspect of the present invention, a method for preparing a molybdenum-manganese metallized ceramic part is provided, comprising the following steps:

[0011] (1) According to the above raw material components, molybdenum powder, manganese powder and porcelain powder are mixed, a binder solution is added, and the mixture is stirred at room temperature to obtain a ceramic molybdenum-manganese metallization slurry;

[0012] (2) The obtained ceramic molybdenum-manganese metallization slurry is coated on the surface of the ceramic body, and then dried and sintered to obtain a metallized ceramic part.

[0013] Furthermore, the coating method includes screen printing, spot coating, spraying, rolling, dipping or sputtering.

[0014] Furthermore, the composition of the ceramic powder is consistent with or close to the composition of the ceramic body.

[0015] Furthermore, the viscosity of the ceramic molybdenum-manganese metallization slurry in step (1) is 1500-6000 mPa·s.

[0016] Furthermore, in step (2), the drying temperature is 40-80° C. and the drying time is 20-60 min.

[0017] Furthermore, in step (2), the sintering temperature is 1480-1580° C., and the holding time is 60-90 min.

[0018] According to another aspect of the present invention, there is provided a metallized ceramic part, wherein the metallized ceramic part is made by the above method.

[0019] Furthermore, the thickness of the metallized layer in the metallized ceramic piece is 5-30 microns, and the relative average deviation of the thickness of the metallized layer in the metallized ceramic piece is less than 2%.

[0020] The present invention has the following beneficial effects:

[0021] The thickness of the molybdenum-manganese metallization layer made of the ceramic metallization slurry provided by the present invention is 5-30 microns, the relative average deviation of the thickness of the entire metal layer is less than 2%, and there is no "groove" in the prior art. The thickness of the molybdenum-manganese metallization layer of the existing process is generally 10-30 microns, and the relative average deviation of the thickness of the entire metal layer is greater than 30%. Compared with the existing process, the molybdenum-manganese dosage of the present invention can be saved by more than 50%, which provides good flatness conditions for nickel coating using the sintered nickel process. There is no need to fill the groove with silver-copper solder, which can save about 50% of the silver-copper precious metal dosage, and the thinner molybdenum-manganese layer can reduce the expansion at high temperature and increase the welding strength. The results of the embodiment of the present invention show that when the thickness of the molybdenum-manganese layer is 10 microns and the thickness of the silver-copper solder sheet is 0.04mm, the welding strength after encapsulation with the metal part reaches 135MPa and above. In addition, the preparation of the ceramic metallization slurry provided by the present invention can be completed at room temperature without heating, which is not only environmentally friendly but also low in cost.

[0022] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 is a surface image of the metallization layer after drying according to Example 1 of the present invention;

[0025] Figure 2 is a scanning electron microscope (SEM) image of the metallized ceramic member of Example 1 of the present invention;

[0026] Figure 3 is a thickness test position diagram of the metallized ceramic part according to Example 1 of the present invention;

[0027] Figure 4 is a surface image of the metallization layer after drying according to Example 2 of the present invention;

[0028] Figure 5 is a scanning electron microscope (SEM) image of the metallized ceramic member of Example 2 of the present invention;

[0029] Figure 6 is a surface image of the metallization layer after drying according to Example 3 of the present invention;

[0030] Figure 7 is a scanning electron microscope (SEM) image of the metallized ceramic member of Example 3 of the present invention;

[0031] Figure 8 This is a surface image of the metallization layer of Comparative Example 1 after drying;

[0032] Fig. 9 is a scanning electron microscope (SEM) image of the metallized ceramic member of Comparative Example 1;

[0033] Fig.10 It is a comparison chart of the welding strength of the packages of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0035] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0036] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and the “multiple” in “one or more” means two or more, and the “multiple” in “one or more” means two or more.

[0037] The embodiment of the first aspect of the present invention provides a ceramic molybdenum-manganese metallization slurry, comprising the following raw material components: ceramic metal powder and a binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is (0.5-3): 1,

[0038] The ceramic metal powder comprises the following components in parts by weight: 60-86 parts of molybdenum powder, 7-20 parts of manganese powder, and 7-20 parts of porcelain powder; the binder solution comprises a binder and water, the mass ratio of the binder to water is (0.2-1.5):1, the binder is a polymer containing both a hydrophilic monomer and a hydrophobic monomer, the mass ratio of the hydrophilic monomer to the hydrophobic monomer is 1:(0.15-18),

[0039] The structural formula of the hydrophobic monomer is CH2=CR 1 R 2 , where R 1 is -H or -CH3; R 2 -CN, -C6H5, -COOR 3 , where R 3 is an alkyl group, a cycloalkyl group or an aromatic group;

[0040] The structural formula of the hydrophilic monomer is: CHR 4 =CR 5 R 6 , where R 4 and R 5 All are -H or -CH3 or -COOM; R 6 -COOM, -CH2COOM, -COO(CH2)6SO3M, -CONH2, -CONHR 7 , where R 7 is an alkyl group or a cycloalkyl group; M is an H element or any one of the metal elements involved in the ceramic metal powder.

[0041] In an embodiment of the present invention, the mass ratio of the ceramic metal powder to the binder solution is (0.5-3):1. For example, the mass ratio of the ceramic metal powder to the binder solution is 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, etc. The mass ratio of the ceramic metal powder to the binder solution can also be any combination range of the above-mentioned numerical values.

[0042] In an embodiment of the present invention, the ceramic metal powder includes the following components in parts by weight: 60-86 parts of molybdenum powder, 7-20 parts of manganese powder, and 7-20 parts of porcelain powder. Among them, the molybdenum powder can be 60 parts, 64 parts, 68 parts, 70 parts, 75 parts, 80 parts or 86 parts, etc., and the mass parts of the molybdenum powder can also be any combination range of the above values. The manganese powder can be 7 parts, 10 parts, 12 parts, 15 parts, 18 parts or 20 parts, etc., and the mass parts of the manganese powder can also be any combination range of the above values. The porcelain powder can be 7 parts, 10 parts, 12 parts, 15 parts, 18 parts or 20 parts, etc., and the mass parts of the porcelain powder can also be any combination range of the above values.

[0043] In an embodiment of the present invention, the binder solution includes a binder and water, and the mass ratio of the binder to the water is (0.2-1.5):1. For example, the mass ratio of the binder to the water is 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1 or 1.5:1, etc. The mass ratio of the binder to the water can also be any combination range of the above values.

[0044] In an embodiment of the present invention, the binder is a polymer having both a hydrophilic monomer and a hydrophobic monomer, and the mass ratio of the hydrophilic monomer to the hydrophobic monomer is 1:(0.15-18), for example, the mass ratio of the hydrophilic monomer to the hydrophobic monomer is 1:0.15, 1:0.5, 1:1, 1:2, 1:5, 1:8, 1:10, 1:12, 1:15 or 1:18, etc. The mass ratio of the hydrophilic monomer to the hydrophobic monomer can also be any combination range of the above values. The binder can play the dispersing function of a surfactant. On the one hand, its hydrophilic group interacts with the ceramic metal powder, and on the other hand, the hydrophobic group uses its hydrophobicity to prevent the material from agglomerating and settling. Therefore, when the mass ratio of the hydrophilic monomer to the hydrophobic monomer is too large or too small, its dispersibility cannot be effectively exerted, resulting in instability and easy sedimentation of the slurry.

[0045] In an embodiment of the present invention, the binder is a polymer having a hydrophilic monomer and a hydrophobic monomer at the same time, wherein the hydrophilic monomer comprises one or more of acrylic acid, acrylate, acrylamide (acrylamide, N-methylacrylamide, N-ethylacrylamide, N-butylacrylamide, 2-methylacrylamide), vinyl sulfonic acid, vinyl sulfonate, methacrylic acid, methacrylate, propylene sulfonic acid, propylene sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, itaconic acid, itaconic acid salt and maleic acid. The hydrophobic monomer comprises one or more of cyclohexyl acrylate, acrylonitrile, styrene, acrylates (methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, octyl acrylate, vinyl acetate, isobornyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, etc.), methacrylonitrile, etc.

[0046] In some embodiments, the binder includes acrylic acid (hydrophilic monomer) and vinyl acetate (hydrophobic monomer), and the preparation method includes: adding 18 parts by mass of acrylic acid and distilled water into a reactor, dissolving under high-speed stirring, adding 12 parts by mass of vinyl acetate, adding an initiator to initiate the reaction at 60°C, and continuously stirring until the reaction is completed to obtain a water-based binder.

[0047] In other embodiments, the binder includes acrylamide (hydrophilic monomer) and butyl acrylate (hydrophobic monomer). The specific preparation method is as follows: 40 parts by weight of acrylamide and distilled water are added into a reaction container, and stirred to dissolve at a speed of 300 r / min; nitrogen is introduced; the mixture is heated to 70°C, and then 60 parts by weight of butyl acrylate is added until the temperature is kept constant at 70°C; then an initiator ammonium persulfate is added to initiate the reaction, and the precipitate is taken out after the reaction for 9 hours, and ammonia water is added to neutralize the pH to 6.5-9 to obtain a water-based adhesive.

[0048] In order to obtain ideal bonding, the adhesive and the adherend must have good wetting. According to Young's wetting equation:

[0049] γ s =γ sl +γ sl cosθ (Equation 1.1)

[0050] and

[0051] W sl =γ s +γ l -γ sl (Formula 1.2)

[0052] Substituting equation 1.2 into equation 1.1, we get

[0053] W sl =γ l (1+cosθ)(Equation 1.3)

[0054] Where: W sl —adhesion between solid and liquid; γ l —Surface tension of liquid in solid medium; γ s —Surface tension of solid in gas medium; γ sl —Surface tension between solid and liquid; θ—contact angle between solid and liquid.

[0055] It can be seen from formula 1.3 that the adhesion between the adhesive and the adherend is mainly affected by surface tension and contact angle. On the other hand, if θ<90°, that is, as the angle becomes smaller, the liquid is more likely to wet the solid; if θ>90°, the liquid becomes spherical and cannot wet the solid, and it is easy to move on the solid surface. When θ=0, the adhesion can reach a maximum value. In real life, θ cannot be 0°, so the contact angle is made as small as possible. On the other hand, it can be seen from formula 1.1 that when θ is as small as possible, γ s =γ l +γ sl Very small and can be ignored, that is, when the surface tension of the liquid is consistent with the surface tension of the solid, there is good wettability.

[0056] In the present invention, the surface tension of the slurry system prepared by the binder mainly depends on the water solvent. Since the viscosity of water is much smaller than that of pineol, that is, the interaction between water molecules is smaller than that of pineol, using water as a solvent can reduce the surface tension of the slurry system, making it close to the surface tension of the ceramic substrate, thereby avoiding the appearance of a groove with thick sides and thin middle due to excessive surface tension of the slurry. At the same time, a large number of functional groups such as carboxyl and hydroxyl groups in the adhesive molecules can form strong physical and chemical forces with the surface components of powder materials such as molybdenum and manganese and the ceramic substrate through adsorption, mutual diffusion, electrostatic action, etc., to achieve a better adhesive effect.

[0057] The thickness of the molybdenum-manganese metallization layer made of the ceramic metallization slurry provided by the present invention is 5-30 microns, the relative average deviation of the thickness of the entire metal layer is less than 2%, and there is no "groove" in the prior art. The thickness of the molybdenum-manganese metallization layer of the existing process is generally 10-30 microns, and the relative average deviation of the thickness of the entire metal layer is greater than 30%. Compared with the existing process, the molybdenum-manganese dosage of the present invention can be saved by more than 50%, which provides good flatness conditions for nickel coating using the sintered nickel process. There is no need to fill the groove with silver-copper solder, which can save about 50% of the silver-copper precious metal dosage, and the thinner molybdenum-manganese layer can reduce the expansion at high temperature and increase the welding strength. The results of the embodiment of the present invention show that when the thickness of the molybdenum-manganese layer is 10 microns and the thickness of the silver-copper solder sheet is 0.04mm, the welding strength after encapsulation with the metal part reaches 135Mpa and above. In addition, the preparation of the ceramic metallization slurry provided by the present invention can be completed at room temperature without heating, which is not only environmentally friendly but also low in cost.

[0058] In an embodiment of the present invention, the particle size of the molybdenum powder and the manganese powder is less than or equal to 10 microns. When the particle size of the molybdenum powder and the manganese powder is greater than 10 microns, the weight is heavy, the slurry stability is poor, and sedimentation is easy to occur.

[0059] The ceramic powder is mainly a mixture that is consistent with or close to the ceramic component during metallization treatment. In some embodiments, the ceramic powder includes a combination of one or more of Al2O3, SiO2, CaO, MgO and MnO2. These ceramic powders will form a glass phase at high temperature to fill the gaps in the molybdenum-manganese metal layer, and because the glass phase is consistent with the ceramic component, it has excellent compatibility, increasing the bonding force and density of the molybdenum-manganese metal layer and the ceramic body.

[0060] In some embodiments, the ceramic powder is composed of Al2O3, SiO2 and CaO, and the mass ratio of Al2O3, SiO2 and CaO is 1:1:1. The ceramic powder is suitable for metallization of 95 alumina ceramic body.

[0061] The second aspect of the present invention provides a method for preparing a metallized ceramic part, comprising the following steps:

[0062] (1) According to the above raw material components, molybdenum powder, manganese powder and porcelain powder are mixed, a binder solution is added, and the mixture is stirred at room temperature to obtain a ceramic metallization slurry;

[0063] (2) The obtained ceramic metallization slurry is coated onto the ceramic surface by screen printing, and then dried and sintered to obtain a metallized ceramic part.

[0064] The preparation method of the metallized ceramic part provided by the present invention can be carried out at room temperature during the preparation process of the ceramic metallization slurry, without the need for heating the slurry, which not only saves costs but is also environmentally friendly and has no effect on the health of operators.

[0065] In some embodiments, the coating method includes screen printing, spot coating, spray coating, roll coating, dip coating or sputtering.

[0066] In some embodiments, the composition of the ceramic powder is consistent with or close to that of the ceramic body. These ceramic powders will form a glass phase at high temperature to fill the gaps in the molybdenum-manganese metal layer, and because the glass phase is consistent with the composition of the ceramic body, it has excellent compatibility, thereby increasing the bonding strength and density of the molybdenum-manganese metal layer and the ceramic body.

[0067] In an embodiment of the present invention, the viscosity of the ceramic metallization slurry in step (1) is 1500-6000 mPa·s. When the viscosity of the ceramic metallization slurry is lower than 1500 mPa·s, the slurry is easy to settle and overflow during coating; when the viscosity is higher than 6000 mPa·s, the fluidity of the slurry deteriorates, the coating cannot be scraped, and the coating is prone to cracking.

[0068] In an embodiment of the present invention, the drying temperature in step (2) is 40-80°C and the drying time is 20-60 minutes. At the above temperature, if the drying time is less than 20 minutes, the food will not be dried. If the drying time is too long, the drying effect will not be further improved, but energy consumption will be increased and production efficiency will be reduced.

[0069] In the embodiment of the present invention, the sintering temperature in step (2) is 1480-1580°C and the holding time is 60-90 minutes. The ceramic metal powder undergoes chemical changes at 1480-1580°C and the holding time is 60-90 minutes. The above is to make the chemical changes more complete. A time higher than 90 minutes has no obvious benefit to the metallization effect, but will increase energy consumption and reduce production efficiency.

[0070] An embodiment of the third aspect of the present invention provides a metallized ceramic part, wherein the metallized ceramic part is made by the above method.

[0071] In an embodiment of the present invention, the thickness of the metallized layer in the metallized ceramic piece is 5-30 microns, and the relative average deviation of the thickness of the metallized layer in the metallized ceramic piece is less than 2%.

[0072] The results of the embodiments of the present invention show that when the thickness of the molybdenum-manganese layer is 10 microns and the thickness of the silver-copper solder sheet is 0.04 mm, the welding strength after packaging with the metal part reaches 135 MPa or above, which is higher than 115 MPa of the comparative example (existing process).

[0073] Example

[0074] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0075] Example 1

[0076] The present embodiment provides a ceramic metallization slurry, comprising the following raw material components: ceramic metal powder and a binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is 1.5:1, wherein the ceramic metal powder comprises the following components in parts by weight: 70 parts of molybdenum powder; 15 parts of manganese powder; and 15 parts of porcelain powder; the binder solution comprises a binder and water, wherein the mass ratio of the binder to the water is 1:1, and the mass ratio of the hydrophilic monomer to the hydrophobic monomer in the binder is 1:18, wherein the hydrophobic monomer is propylene acrylonitrile, and the hydrophilic monomer is acrylate, and the binder is prepared by copolymerizing propylene acrylonitrile and acrylate in an aqueous phase.

[0077] The method for preparing a metallized ceramic part using the above raw materials comprises the following steps:

[0078] (1) According to the above raw material components, molybdenum powder, manganese powder and porcelain powder are mixed, a binder solution is added, and the mixture is stirred at room temperature to obtain a ceramic metallization slurry; the viscosity of the ceramic metallization slurry is 2460 mPa·s.

[0079] (2) The obtained ceramic metallization slurry is applied to the surface of the ceramic part by screen printing, wherein the screen is 200 mesh, and then dried and sintered to obtain a metallized ceramic part. The drying temperature in step (2) is 60°C and the drying time is 40 minutes. The sintering temperature in step (2) is 1500°C and the insulation time is 75 minutes. The ceramic part is a ceramic ring with a diameter of 8 mm, a wall thickness of 0.8 mm and a height of 10 mm, and the molybdenum-manganese metallization is processed on the end face of the ceramic ring.

[0080] Figure 1 This is the surface image after the metallization layer is dried. Figure 1 It can be seen that the surface of the metal layer is uniform and flat.

[0081] Figure 2 This is a scanning electron microscope (SEM) image of a metallized ceramic part. It can be seen from the image that the thickness of the surface layer is relatively uniform, about 10 microns.

[0082] Use XRF coating thickness gauge to perform non-destructive metal layer thickness testing at different locations. Figure 3 As shown, the test data is shown in Table 1 below.

[0083] Table 1 Comparison of thickness differences in different areas of the embodiment

[0084]

[0085] Example 2

[0086] The present embodiment provides a ceramic metallization slurry, comprising the following raw material components: ceramic metal powder and a binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is 0.5:1, wherein the ceramic metal powder comprises the following components in parts by weight: 65 parts of molybdenum powder; 7 parts of manganese powder; and 10 parts of porcelain powder; the binder solution comprises a binder and water, wherein the mass ratio of the binder to water is 1.5:1, and the mass ratio of a hydrophilic monomer to a hydrophobic monomer in the binder is 1:0.15, wherein the hydrophobic monomer is styrene, and the hydrophilic monomer is methacrylic acid, and the binder is prepared by copolymerizing styrene and methacrylic acid in an aqueous phase.

[0087] The above raw materials are used to prepare metallized ceramic parts. The preparation method of the ceramic parts is the same as that of Example 1.

[0088] Figure 4 This is the surface image after the metallization layer is dried. Figure 1 It can be seen that the surface of the metal layer is uniform and flat.

[0089] Figure 5 This is a scanning electron microscope (SEM) image of a metallized ceramic part. It can be seen from the image that the thickness of the surface layer is relatively uniform, about 10 microns.

[0090] The non-destructive metal layer thickness test was performed using an XRF coating thickness gauge at different positions. The test positions refer to those in Example 1. The test data is shown in Table 2 below.

[0091] Table 2 Comparison of thickness differences in different areas of Example 2

[0092]

[0093] Example 3

[0094] The present embodiment provides a ceramic metallization slurry, comprising the following raw material components: ceramic metal powder and a binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is 3:1, wherein the ceramic metal powder comprises the following components in parts by weight: 86 parts of molybdenum powder; 18 parts of manganese powder; and 7 parts of porcelain powder; the binder solution comprises a binder and water, wherein the mass ratio of the binder to water is 0.2:1, and the mass ratio of the hydrophilic monomer to the hydrophobic monomer in the binder is 1:9, wherein the hydrophobic monomer is isobornyl acrylate, and the hydrophilic monomer is 2-acrylamide-2-methylpropane sulfonic acid, and the binder is prepared by copolymerizing isobornyl acrylate and 2-acrylamide-2-methylpropane sulfonic acid in an aqueous phase.

[0095] The above raw materials are used to prepare metallized ceramic parts. The ceramic parts and the preparation method are the same as those in Example 1.

[0096] Figure 6 This is the surface image after the metallization layer is dried. Figure 1 It can be seen that the surface of the metal layer is uniform and flat.

[0097] Figure 7 This is a scanning electron microscope (SEM) image of a metallized ceramic part. It can be seen from the image that the thickness of the surface layer is relatively uniform, about 10 microns.

[0098] The non-destructive metal layer thickness test was performed using an XRF coating thickness gauge at different positions. The test positions refer to those in Example 1. The test data is shown in Table 3 below.

[0099] Table 3 Comparison of thickness differences in different areas of Example 3

[0100]

[0101] Comparative Example 1

[0102] (1) Molybdenum powder, manganese powder and porcelain powder are mixed in an amount of 70 parts, 15 parts and 15 parts respectively to obtain ceramic metal powder;

[0103] (2) adding 4 parts of ethyl cellulose to 100 parts of pine alcohol at 60° C. and stirring to form a binder solution;

[0104] (3) 10 parts of ceramic metal powder and 3 parts of binder solution were added to a ball mill, and stirred and ball milled at 60° C. for 24 hours to obtain a relatively uniform slurry, wherein the viscosity of the ceramic metallization slurry was 5000 mPa·s. ;

[0105] (4) The remaining methods are the same as those in Example 1, and the ceramic part is the same as that in Example 1, to obtain a metallized ceramic part.

[0106] Figure 8 This is the surface image after the metallization layer is dried. Figure 1 It can be seen that the surface of the metal layer presents obvious grooves.

[0107] Fig. 9 This is a scanning electron microscope (SEM) image of a metallized ceramic part.

[0108] The non-destructive metal layer thickness test was performed using an XRF coating thickness gauge at different positions. The test positions refer to those in Example 1. The test data is shown in Table 4 below.

[0109] Table 4 Comparison of thickness differences in different areas of Comparative Example 1

[0110]

[0111] The metallized ceramic parts and metal parts prepared in Examples 1 to 3 and Comparative Example 1 are packaged, and the packaging method is as follows:

[0112] (1) electroplating a layer of electrodeposited nickel with a thickness of about 3 to 5 microns on the surface of the molybdenum-manganese metal layer of the ceramic part having been metallized with molybdenum-manganese;

[0113] (2) Use a 0.08 mm thick silver-copper solder sheet as solder, place it between the metallized ceramic part deposited with a nickel metal layer and the metal part to be welded, and perform high-temperature welding at about 850°C in a vacuum or inert atmosphere or a reducing atmosphere to achieve packaging.

[0114] The welding strength test was performed on the encapsulated parts of Examples 1 to 3 and Comparative Example 1. The test method was based on the national industry standard (JC / T2681-2022). The welding strength of the metallized ceramic parts and metal parts of Examples 1 to 3 after encapsulation reached 135 MPa or above, while the welding strength of Comparative Example 1 was only 115 MPa. Fig.10 shown.

[0115] Although the present invention has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A ceramic molybdenum-manganese metallization slurry, characterized in that: The invention comprises the following raw material components: ceramic metal powder and binder solution, wherein the mass ratio of the ceramic metal powder to the binder solution is (0.5-3): 1, The ceramic metal powder comprises the following components in parts by weight: 60-86 parts of molybdenum powder, 7-20 parts of manganese powder, and 7-20 parts of porcelain powder; the binder solution comprises a binder and water, the mass ratio of the binder to water is (0.2-1.5):1, the binder is a polymer containing both a hydrophilic monomer and a hydrophobic monomer, the mass ratio of the hydrophilic monomer to the hydrophobic monomer is 1:(0.15-18), The structural formula of the hydrophobic monomer is CH2=CR 1 R 2 , where R 1 is -H or -CH3; R 2 -CN, -C6H5, -COOR 3 Any one of the following, where R 3 is any one of an alkyl group, a cycloalkyl group, and an aromatic group; The structural formula of the hydrophilic monomer is: CHR 4 =CR 5 R 6 , where R 4 is -H or -CH3 or -COOM; R 5 is -H or -CH3 or -COOM; R 6 -COOM, -CH2COOM, -COO(CH2)6SO3M, -CONH2, -CONHR 7 Any one of the following, where R 7 is an alkyl group or a cycloalkyl group; M is an H element or any one of the metal elements involved in the ceramic metal powder.

2. The ceramic molybdenum-manganese metallization slurry according to claim 1, characterized in that: The particle size of the molybdenum powder and the manganese powder is less than or equal to 10 microns.

3. A method for preparing a metallized ceramic part, characterized in that: The steps include: (1) According to the raw material components of claim 1 or 2, molybdenum powder, manganese powder and porcelain powder are mixed, a binder solution is added, and the mixture is stirred at room temperature to obtain a ceramic molybdenum-manganese metallization slurry; (2) coating the obtained ceramic molybdenum-manganese metallization slurry onto the surface of the ceramic body, and then drying and sintering the sintering temperature at 1480-1580° C. for 60-90 min to obtain a metallized ceramic part; The thickness of the metallized layer in the metallized ceramic part is 5-30 microns, and the relative average deviation of the thickness of the metallized layer in the metallized ceramic part is less than 2%.

4. The method for preparing a metallized ceramic part according to claim 3, characterized in that: Application methods include screen printing, dispensing, spraying, rolling, dipping or sputtering.

5. The method for preparing a metallized ceramic part according to claim 3, characterized in that: The composition of the ceramic powder is consistent with the composition of the ceramic body.

6. The method for preparing a metallized ceramic part according to claim 3, characterized in that: The viscosity of the ceramic molybdenum-manganese metallization slurry in step (1) is 1500-6000 mPa·s.

7. The method for preparing a metallized ceramic part according to claim 3, characterized in that: In step (2), the drying temperature is 40-80°C and the drying time is 20-60 min.

8. A metallized ceramic part, characterized in that: The metallized ceramic part is made by the preparation method of any one of claims 3 to 7.

Citation Information

Patent Citations

  • Metal transition layer suitable for zirconia ceramic and metal welding and preparation method

    CN114538948A